Dirección del talento humano y su incidencia en la calidad del servicio en el gobierno autónomo descentralizado provincial de Los Ríos, periodo 2020. plan de formación continua - Estupiñan Loor, Diana Carolina (2021)
The document shows the study on the management of human talent and its impact on the quality of services in the Autonomous Decentralized Provincial Government of Los Ríos, for the purpose of the research, a documentary and field type investigation was carried out, In order to compile the necessary information on the management of human talent in the institution, which led to the implementation of surveys and interviews with a sample obtained from the personnel working in said organization, in the same way, it was determined how the lack of work commitment and what inconveniences have arisen in the customer service, considering the most relevant aspects of this service. With the results obtained, it is hoped to improve the service of users, training the personnel in charge, for this, a continuous training plan has been proposed "Teaching Technical Guide" to improve the management of Human Talent in the Provincial Decentralized Autonomous Government de Los Ríos, considering all the recommendations contained in the section and making possible the development of the proposal, to achieve efficiency and effectiveness in the development of administrative and operational processes, especially in the improvement of care and services to users. This research starts from the management of human capital as a whole, integrating processes designed to plan, develop, motivate better performance in the service delivery functions in the institution, and comply with the users of the province, whose function is the positive impact that They are provided with employees, technicians, managers committed and involved with the vision and mission of the Provincial GAD of Los Ríos. The need for the organization to be oriented towards a more ambitious vision of human resources is concluded, linking them as key elements of the strategic direction for institutional success. Keywords: management, human talent, efficiency, effectiveness and services.